Rockburst Disaster Prediction of Isolated Coal Pillar by Electromagnetic Radiation Based on Frictional Effect - Tongbin Zhao; Yanchun Yin; Fukun Xiao; Yunliang Tan; Jianchao Zou (The Scientific World Journal)
Based on the understanding that charges generated during coal cracking are due to coal particle friction, a microstructure model was developed by considering four different variation laws of friction coefficient. Firstly, the frictional energy release of coal sample during uniaxial compressive tests was investigated and discussed. Then electromagnetic radiation method was used to predict the potential rockburst disaster in isolated coal pillar mining face, Muchengjian Colliery. The results indicate that the friction coefficient of coal particles decreases linearly with the increase of axial loading force. In predicting the strain-type rockburst, the high stress state of coal must be closely monitored. Field monitoring shows that electromagnetic radiation signal became abnormal before the occurrence of rockburst during isolated coal pillar mining. Furthermore, rockburst tends to occur at the early and ending stages of isolated coal pillar extraction. Mine-site investigation shows the occurrence zone of rockburst is consistent with the prediction, proving the reliability of the electromagnetic radiation method to predict strain-type rockburst disaster.